(untitled) (Italian Review of Legal History, 2024)
With the rise of industrial and financial capitalism and the expansion of international trade thanks to technical progress during the late 19th and early 20th centuries, the protection of private property in maritime warfare was called into question on economic, legal and political grounds. Western jurists did not shy away from the debate, which took place in institutions - notably the Institut de droit international - and in university teaching. Through studies, writings and active political participation, many of them argued about the freedom of trade and the protection of private property; they tried to point out ways to abolish or at least better regulate the right to prize at sea; to supervise the control of maritime trade; to regulate war smuggling. The wishes were rarely translated into concrete results and clashed with established customs and practices. The essay focuses on the informed, pragmatic and disillusioned narrative of Tullio Giordana (1877-1950), a lawyer by training and a journalist and publicist by profession.